Levodopa versus levodopa sparing in early parkinson's disease: can we meet halfway? - Mayela Rodríguez-Violante; Ana J. Hernández-Medrano; Amin Cervantes-Arriaga; Cesarina Torres-Vásquez; Dioselina Tristán-Samaniego; Carolina Zepeda-Salazar; Victoria Cerino-Palomino; Arturo Abundes-Velasco (Permanyer, 2024)
Monotherapy is the recommended initial treatment for early Parkinson's disease. The pharmacological options for initial treatment include dopaminergic agonists, monoamine oxidase B inhibitors, and levodopa formulations. Several factors should be considered when selecting the optimal treatment, such as disease severity, disease duration, age, activity level, and the risk of developing motor and non-motor complications. Early evidence on the potential role of levodopa formulations in the risk of dyskinesia led to levodopa aversion in the late 1990s and early 2000s, favoring the use of levodopa-sparing options like dopamine agonists. This shift resulted in an increase in behavioral adverse effects, such as impulse control disorders, leading to a subsequent dopamine agonist aversion in the mid-2000s. This review aims to provide a comprehensive evaluation of the existing literature regarding the benefits and drawbacks of levodopa versus levodopa-sparing strategies in drug-naive early-stage Parkinson's disease.